Pengaruh Motivasi Kerja Dan Gaya Kepemimpinan Terhadap Produktivitas Pekerja Di Pt. Hayyu Pratama Kaltim - Saputra, Adi Nugraha; Jubaidi; Rinda Sandayani Karhab (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the influence of work motivation and leadership style on worker productivity at PT. Hayyu Pratama Kaltim. The background of this research is based on the importance of productivity as a performance indicator in the construction services sector, as well as the emergence of issues related to motivation and leadership style within the company. The research method used is a quantitative approach with a survey technique through the distribution of questionnaires to 48 respondents out of a total of 92 permanent employees, selected using simple random sampling. Data analysis was conducted using multiple linear regression, t-test, F-test, and coefficient of determination. The results of the study indicate that leadership style has a positive and significant effect on productivity, while work motivation has a positive but insignificant effect. Simultaneously, both variables have a significant effect on productivity with a contribution of 38.7%, while the remainder is influenced by other factors. These findings indicate that leadership style is the dominant factor in improving worker productivity. The implications of this study highlight the importance of developing effective leadership and improving motivation systems to support enhanced workforce performance in the construction sector.